(untitled) (Altre Modernità, 2025)
The aim of this essay is to explain the success of Antonio Manzini’s narrative ‘series’ centered on the character of Rocco Schiavone, which is due to the complexity with which the character was outlined and to the ability to blend the structural elements typical of the ’series’ with some typical elements of the ‘saga’. The analysis is conducted through the reconstruction of Manzini’s narrative career and through a comparison between the character of Schiavone and the character of Montalbano, created by Andrea Camilleri.